A study to assess the awareness and knowledge about the maternal nutrition and complications encountered by the antenatal mothers in the rural population - S., Sindhu; D., Vidhya; K., Sivankumar; M. A., Karthiga (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Nutrition plays a vital role in life. Good nutrition is an important part of leading a healthy lifestyle. A healthy pregnancy diet will promote your baby’s growth and development. The purpose of this study was to highlight the knowledge, attitude and practices of pregnant women regarding the healthy diet, psychological support, regular visits, danger signs and complications during pregnancy among mothers who visit our hospital along with different socio demographic factors. Methods: This study was conducted on 350 antenatal women from January 2016 to February 2017 at Tamil Nadu, India. A 24 point- 15 minutes’ questionnaire was designed about the knowledge, attitude and practice about the nutrition, danger signs and complications in pregnancy. Results: Around 98% of women were very clear that nutrition is necessary in pregnancy and 53% of them told that the quantity of food intake should be increased. Major source of knowledge about the nutrition was obtained from the family members (81%). The common danger sign was abdominal pain (61%) followed by bleeding per vaginum (22%). About 77% of mothers had an idea that minimum of 6-10 visit should be there in their antenatal period. Conclusions: This study emphasizes that health professionals should concentrate more in the nutritional values and the antenatal classes should be taken regarding the role of adequate nutrition, constituents and sources of balanced diet and the consequences of over and under nutrition.